Human rights at the grassroots ideals, realities, prospects - Domingo, Ma. Oliva Z. (2011)
The establishment of the Barangay Human Rights Action Center (BHRAC), which started out as a social action program in the early 1990s, was envisioned to empower human rights advocates at the community level to promote and uphold human rights themselves. All barangays, through the Department of Interior and Local Government, are enjoined to establish BHRACs to undertake functions related to human rights protection and promotion such as complaints processing, information and advocacy, and coordination center on human rights issues at the barangay level. This study assesses the effectivity and functionality of the BHRAC as the flagship program of the Commission on Human Rights in bringing the Commission's services to the grassroots. Focusing on BHRAC and the performance of the Barangay Human Rights Action Officers (BHRAOs), the assessment covered 24 barangays around the Philippines. The study devices a framework that identifies the functionality and sustainability mechanisms of the BHRAC/BHRAO for the promotion and protection of human rights. The study approach to identify performance gaps, problem areas, and factors that affect the performance of BHRACs and BHRAOs of their functions.
Keywords: Human rights; Local government; Commission on Human Rights; Human rights -- Political aspects; Civil rights; Human rights workers; Barangay Human Rights Action Center; Barangay Human Rights Action Officers